Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.21203/rs.3.rs-1372619/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The co-administration of live fowlpox and Newcastle disease vaccines by non-invasive routes to chickens reared by smallholders in Tanzania and Nepal.

Abstract: The co-administration of commercial live fowlpox (FP) and Newcastle disease (ND) vaccines when given by non-invasive (needle-free) routes was demonstrated to be safe and to elicit immunity in two field studies, one in Tanzania the other in Nepal. Both studies were of a cluster-randomised controlled design in which birds were randomly assigned to one of five treatment groups: (i) administration with FP vaccine alone (feather follicle), (ii) administration with ND vaccine alone (eye-drop), (iii) concurrent admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…An earlier study from Nepal showed that LaSota strain vaccination in village chickens is immunogenic and efficacious against NDV infection [21]. A recent study also showed that LaSota vaccination was safe and induced a protective level of antibodies in 98% of vaccinated birds at 28 days post-vaccination [22]. Field verification study of ND I-2 vaccine also showed that it can induce protective levels of antibodies in 50-100% of birds at different study locations [23].…”
Section: Discussionmentioning
confidence: 96%
“…An earlier study from Nepal showed that LaSota strain vaccination in village chickens is immunogenic and efficacious against NDV infection [21]. A recent study also showed that LaSota vaccination was safe and induced a protective level of antibodies in 98% of vaccinated birds at 28 days post-vaccination [22]. Field verification study of ND I-2 vaccine also showed that it can induce protective levels of antibodies in 50-100% of birds at different study locations [23].…”
Section: Discussionmentioning
confidence: 96%